Viabilitas Biji Kakao (Theobroma cacao L.) Perkebunan Rakyat Lombok Utara pada Berbagai Tingkat Kematangan: Implikasi Ekonomi dan Keberlanjutan - Santoso, Bambang Budi; Jayaputra, Jayaputra; Jaya, I Komang Damar (LPPM Universitas Mataram, 2025)
This study aimed to evaluate the effect of cocoa pod maturity on seed viability and early seedling growth in smallholder plantations of North Lombok, and its implications for economic efficiency and sustainability. The experiment was conducted using a factorial randomized complete design with three cocoa genotypes (Genotype-1, Genotype-2, and MCC-02) and three pod maturity levels (140, 150, and 170 days after flowering/DAF). The results indicated that seeds from physiologically mature pods (140 DAF) had the highest viability (germination rate 89.2% and normal seedlings 82.2%), whereas overripe pods (170 DAF) showed a significant decline (65.8% and 46.6%). Seedling growth up to two months was not significantly affected by pod maturity. Harvesting at 140–150 DAF proved more economically efficient by reducing nursery costs, while also supporting sustainability through the availability of high-quality seedlings without land expansion. These findings highlight the importance of appropriate harvest timing to enhance productivity and sustain smallholder cocoa production systems.